HIV, psychological resilience, and substance misuse during the COVID-19 pandemic: A multi-cohort study. (1st February 2022) - Baum, Marianna K.; Tamargo, Javier A.; Diaz-Martinez, Janet; Delgado-Enciso, Ivan; Meade, Christina S.; Kirk, Gregory D.; Mehta, Shruti H.; Moore, Richard; Kipke, Michele D.; Shoptaw, Steven J.; Mustanski, Brian; Mandler, Raul N.; et al.
Abstract: Objective: The COVID-19 pandemic has dramatically impacted mental health, increasing rates of substance misuse. Resilience is a positive adaptation to stress that may act as a buffer against adverse mental health outcomes. Based on prior knowledge, we hypothesized that PLWH would display higher resilience than HIV-uninfected peers, and that high resilience would be associated with lower risk of substance misuse. Methods: This analysis of the Collaborating Consortium of Cohorts Producing NIDA Opportunities (C3PNO) included data from six USA cohorts that administered a COVID-19-related survey with a 3-month follow-up during May 2020 and March 2021. All data was self-reported. The Brief Resilience Scale and General Anxiety Disorder-7 were utilized. Primary analyses consisted of multivariate generalized linear mixed models with random intercepts using binary logistic regression. Results: A total of 1430 participants completed both surveys, of whom 670 (46.9%) were PLWH. PLWH had lower odds of anxiety (OR=0.67, 95% CI: 0.51–0.89) and higher odds of high resilience (OR=1.21, 95% CI: 1.02–1.44) than HIV-uninfected participants, adjusted for covariates. The presence of anxiety was associated with higher risk of misuse of all substances. High resilience was associated with lower risk of anxiety and misuse of substances, adjusted for covariates. Conclusions: Psychological resilience was associated with lower risk of anxiety and substance misuse, potentially serving as a buffer against poor mental and behavioral health during the COVID-19 pandemic. Further research is needed to identify pathways of resilience in the context of substance misuse and comprehensive resilience-focused interventions. Highlights: The COVID-19 pandemic has dramatically impacted mental health, increasing rates of substance misuse. Psychological resilience may act as a buffer against adverse mental and behavioral health problems in people living with HIV. We assessed psychological resilience, anxiety, and substance misuse during the COVID-19 pandemic among six USA cohorts. Resilience was higher among people living with HIV and was associated with lower risk of anxiety and substance misuse.